Analysis of the role and position of the two Christian states (Castile and Aragon) in ending the rule of the Nasrid dynasty in Spain (Damascus University Journal of arts and humanities sciences, 2022)
The Christian governments of the Iberian Peninsula became aware of the formation of a new government in Granada, Spain, on the 26th of Ramadan, 629 AH. Muhammad ibn Yusuf ibn Nasr, while corresponding with the court of Castile, promised that he would continue to be a citizen of that state, provided that the court of Castile recognized the legitimacy of his rule. His successors, by adopting a moderate policy with the Christian governments, tried to re-develop Islam in the Spanish peninsula as before. The present discourse seeks to examine the 270-year history of Bani-Nasr; Explain the role and position of the Spanish Christian states in the fall and elimination of the Bani Nasr dynasty in the Iberian Peninsula by adescriptive-analytical method after examining the written documents, and with this question the existential nature of the role and position of the policies of the governments. What is a Christian in exchange for the removal of the rule of the Bani Nasr family of Granada for several years? Preliminary research shows that the Christian governments of Spain united and befriended each other to eradicate the last representative of the Muslim governments in Spain, the Bani Nasr dynasty, forever. In order to achieve this, they use erosive wars, divisive policies,as well as intimidation, local and regional riots, support for internal unrest, and the spread of a European culture of nudity. , Propagation of Christianity, Influence of Christian Princes in the Court of Bani Nasr, etc. Gradually weakened the Islamic structure of the Bani Nasr dynasty in the region, and using the challenges in the court, especially in replacing the grounds for the fall and elimination of this dynasty. They provided a Muslim ruler in Spain.
Keywords: Bani Nasr family; Castile; persecution policies; Spain; Granada.